Studying Brugada Syndrome With an SCN1B Variants in Human-Induced Pluripotent Stem Cell-Derived Cardiomyocytes - El-Battrawy, Ibrahim; Müller, Jonas; Zhao, Zhihan; Cyganek, Lukas; Zhong, Rujia; Zhang, Feng; Kleinsorge, Mandy; Lan, Huan; Li, Xin; Xu, Qiang; Huang, Mengying; Liao, Zhenxing; et al. (Frontiers in Cell and Developmental Biology, 2019)
Background Among rare channelopathies BrS patients are at high risk of sudden cardiac death (SCD). SCN5A mutations are found in a quarter of patients. Other rare gene mutations including SCN1B have been implicated to BrS. Studying the human cellular phenotype of BrS associated with rare gene mutation remains lacking. Objectives We sought to study the cellular phenotype of BrS with the SCN1B gene mutations using human-induced pluripotent stem cell (hiPSCs)–derived cardiomyocytes (hiPSC-CMs). Methods and results A BrS patient suffering from recurrent syncope harboring a compound mutation (c.629T>C and c.637C>A) in SCN1B, which encodes the function-modifying sodium channel beta1 subunit, and three independent healthy subjects were recruited and their skin biopsies were used to generate hiPSCs, which were differentiated into cardiomyocytes (hiPSC-CMs) for studying the cellular electrophysiology. A significantly reduced peak and late sodium channel current (INa) and a shift of activation curve to more positive potential as well as a shift of inactivation curve to more negative potential were detected in hiPSC-CMs of the BrS patients, indicating that the SCN1B mutations impact the function of sodium channels in cardiomyocytes. The reduced INa led to a reduction of amplitude (APA) and upstroke velocity (Vmax) of action potentials. Ajmaline, a sodium channel blocker, showed a stronger effect on APA and Vmax in BrS cells as compared to cells from healthy donors. Furthermore, carbachol was able to increase arrhythmia events and the beating frequency in BrS. Conclusions Our hiPSC-CMs from a BrS-patient with a compound mutation in SCN1B recapitulated some key phenotypic features of BrS and can provide a platform for studies on BrS with SCN1B mutations.